Stigma Masyarakat Terhadap Penderita Gangguan Jiwa: Tinjauan Literatur - Wahyu Aulizalsini Alurmei (World Health Digital Journal, 2025)
This study aims to identify and analyze the forms of stigma that develop in the community towards people with mental disorders. The data was taken from research articles published in both national and international journals in the last five years (2020–2025). The results of the analysis show that stigma against individuals with mental disorders is still often found, this can be seen through the emergence of negative stereotypes, labeling, discriminatory acts, and false assumptions that are mystical. This stigma has a detrimental impact on the well-being of sufferers and their families, especially in terms of limited access to health services, employment opportunities, and social relationships. Some of the main factors that cause this stigma are low public understanding of mental health, lack of appropriate information, and lack of community-based educational programs, so it is necessary to have a strategy in the form of mental health education, strengthening social support, and implementing intervention programs that work together to reduce stigma that develops in society.